Direct in situ synthesis of a 3D interlinked amorphous carbon nanotube/graphene/BaFe12O19 composite and its electromagnetic wave absorbing properties. Issue 26 (10th March 2017) - Zhao, Tingkai; Ji, Xianglin; Jin, Wenbo; Wang, Chuan; Ma, Wenxiu; Gao, Junjie; Dang, Alei; Li, Tiehu; Shang, Songmin; Zhou, Zhongfu
Abstract : The 3D interlinked amorphous carbon nanotube (ACNT)/reduced graphene oxide (RGO)/BaFe12 O19 (BF) composite was directly prepared by a self-propagation combustion process. Abstract : The 3D interlinked amorphous carbon nanotube (ACNT)/reduced graphene oxide (RGO)/BaFe12 O19 (BF) composite was directly prepared by a self-propagation combustion process. The RGO was synthesized in situ through the massive heat release during the auto-combustion reaction. The interlinked ACNTs and graphene as well as BF formed the conductive networks for improving the dielectric and magnetic loss. The reflection loss peak of ACNT/RGO/BF composite was −19.03 dB at 11.04 GHz in the frequency range of 2–18 GHz. The frequency bandwidth of the reflection loss below −10 dB was 3.8 GHz. The 3D interlinked ACNT-RGO structure, which was composed of dense intertwined ACNT and graphene with quantities of dihedral angles, could consume incident waves via multiple reflections inside the 3D structures. The high conductivity of 3D interlinked ACNT/RGO networks would lead to energy dissipation in the form of heat through molecular friction and dielectric loss.